2018
DOI: 10.1590/0001-3765201820170569
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of stem form and volume through machine learning

Abstract: Taper functions and volume equations are essential for estimation of the individual volume, which have consolidated theory. On the other hand, mathematical innovation is dynamic, and may improve the forestry modeling. The objective was analyzing the accuracy of machine learning (ML) techniques in relation to a volumetric model and a taper function for acácia negra. We used cubing data, and fit equations with Schumacher and Hall volumetric model and with Hradetzky taper function, compared to the algorithms: k n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
10
0
2
Order By: Relevance
“…Among the many existing models for expressing wood volume as a function of diameter and height. The model proposed by Schumacher and Hall [ 8 ] is one of the most widespread in the forestry area due to its statistical properties since it almost always results in unbiased estimates [ 29 , 37 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the many existing models for expressing wood volume as a function of diameter and height. The model proposed by Schumacher and Hall [ 8 ] is one of the most widespread in the forestry area due to its statistical properties since it almost always results in unbiased estimates [ 29 , 37 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the many existing models for expressing wood volume as a function of diameter and height. The model proposed by Schumacher and Hall [8] is one of the most widespread in the forestry area due to its statistical properties since it almost always results in unbiased estimates [29,37,43]. TVb and TVw = total volume with and without bark; V5b and V5w = volume with and without bark up to the commercial diameter of 5 cm; V10b and V10w = volume with and without bark up to the commercial diameter of e 10 cm; V15b and V15w = volume with and without bark up to the commercial diameter of 15 cm; V20b and V20w = volume with and without bark up to the commercial diameter of 20 cm.…”
Section: Schumacher and Hall Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the tested machine learning methods, RF was slightly better than the other methods and its results were similar to the results obtained with multiple linear regression. The assessment of ANN, k nearest neighbors, and RF for modeling trunk shape and volume in black wattle plantation, [18] showed that ANN and RF presented the best results, with RMSE of 8% and 8.4%, respectively, against the RMSE of 9.15% for the polynomial model. The authors concluded that the machine learning techniques are appropriate for forest modeling, however, their use should be cautious because of the greater possibility of overtraining and overfitting.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos a respeito da espécie acácia-negra apresentam-se em certos trabalhos como: Schneider et al (2000), Schneider;Tonini (2003), Sanquetta et al (2015c), Sanquetta et al (2016b) e Schikowski et al (2018). Demonstrando a importância da espécie e de se abranger maiores conhecimentos sobre acácia-negra.…”
Section: Introductionunclassified